2023
DOI: 10.1097/pcc.0000000000003184
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Social Determinants of Health in Pediatric Sepsis Studies*

Abstract: OBJECTIVE:Standardized, consistent reporting of social determinants of health (SDOH) in studies on children with sepsis would allow for: 1) understanding the association of SDOH with illness severity and outcomes, 2) comparing populations and extrapolating study results, and 3) identification of potentially modifiable socioeconomic factors for policy makers. We, therefore, sought to determine how frequently data on SDOH were reported, which factors were collected and how these factors were defined in studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Social determinants of health (SDOH) in pediatric sepsis studies are not commonly reported, with marked variability in categorizations and definitions of SDOH variables. Standardized reporting of SDOH in pediatric sepsis studies is needed to understand the role these factors play in the development, progression, and recovery of sepsis, to implement policies aimed at addressing socioeconomic conditions related to sepsis (36). Actionable solutions to the considerations above are described in Table 1 and include individualized approaches dependent on setting, affordable diagnostics for accurate risk stratification, optimization of data capture from routinely collected datasets to support collaborative registries, and development of locally relevant outcome measures.…”
Section: New Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social determinants of health (SDOH) in pediatric sepsis studies are not commonly reported, with marked variability in categorizations and definitions of SDOH variables. Standardized reporting of SDOH in pediatric sepsis studies is needed to understand the role these factors play in the development, progression, and recovery of sepsis, to implement policies aimed at addressing socioeconomic conditions related to sepsis (36). Actionable solutions to the considerations above are described in Table 1 and include individualized approaches dependent on setting, affordable diagnostics for accurate risk stratification, optimization of data capture from routinely collected datasets to support collaborative registries, and development of locally relevant outcome measures.…”
Section: New Considerationsmentioning
confidence: 99%
“…Social determinants of health (SDOH) in pediatric sepsis studies are not commonly reported, with marked variability in categorizations and definitions of SDOH variables. Standardized reporting of SDOH in pediatric sepsis studies is needed to understand the role these factors play in the development, progression, and recovery of sepsis, to implement policies aimed at addressing socioeconomic conditions related to sepsis ( 36 ).…”
Section: Resources and Accessmentioning
confidence: 99%
“…This month’s special topic for reading review is the recent material PCCM has published on SDOH. Begin with this month’s secondary analysis of a systematic review on physiologic criteria for pediatric sepsis (19): the authors from the Pediatric Sepsis Definition Taskforce reviewed 106 papers and present their prior findings in relation to the World Health Organization SDOH categories. The accompanying editorial is a landmark publication in my view–please read (20).…”
Section: “Pccm Connections” For Readersmentioning
confidence: 99%
“…This month’s special topic for educational review is management of severe illness in resource-limited settings. Start with this month’s Special Article about operationalizing appropriate sepsis definitions in children, worldwide, with an emphasis on low- and middle-income (LMIC) settings (18); the article comes from the Society of Critical Care Medicine Pediatric Sepsis Definition Taskforce (19, 20). Follow this introduction to sepsis practice in LMIC settings by reviewing two reports from PCCM 2021 about severity of illness.…”
Section: “Pccm Connections” For Readersmentioning
confidence: 99%